Comparison between content marketing and paid marketing / Dr. Sarah Sabir Ahmad, Dr. Azfahanee Zakaria and Anis Liyana Mohd Arif - Sabir Ahmad, Sarah; Zakaria, Azfahanee; Mohd Arif, Anis Liyana (Universiti Teknologi MARA, Kedah, 2022)
In this new era of globalization, almost all businesses that are either online or offline use various types of marketing strategies in order to boost their business especially after the downturn faced by many during the pandemic Covid-19 attack that happened all around the world in 2020. Since the first COVID-19 case happened in Malaysia, Malaysia's Prime Minister announced a movement control order (MCO) started on 18 March (Tang, 2020). For that matter, all sectors needed to shut down their business. To survive, business owners, especially those who run an offline business previously were obligated to switch to online business. Even if the offline business owner did not know different types of ways to market their products through online marketing, they had to learn how to do it anyway for survival. Research showed that many business owners shared their online business started with their friends on Whatsapp (Holovach, 2022). They also started to create social media like Facebook and Instagram and learned how to use social media platforms in order to boost their sales. On the other hand, for online businesses who already started with online marketing before the pandemic, it was not a big deal for them because it was already their cup of tea. They only needed to step up their marketing techniques due to the increase of the number of new entrants at that time.